2008
DOI: 10.1103/physreve.77.051909
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between a phase response curve and spike-timing-dependent plasticity leading to wireless clustering

Abstract: A phase response curve (PRC) characterizes the signal transduction between oscillators such as neurons on a fixed network in a minimal manner, while spike-timing-dependent plasiticity (STDP) characterizes the way of rewiring networks in an activity-dependent manner. This paper demonstrates that these two key properties both related to the interaction times of oscillators work synergetically to carve functionally useful circuits. STDP working on neurons that prefer asynchrony converts the initial asynchronous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Previous work showed that STDP can induce non-trivial synchrony structure between neurons (Câteau et al 2008), and that dendritic delays play an important role (Senn et al 2002;Lubenov and Siapas 2008). The present framework can be adapted to incorporate these aspects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work showed that STDP can induce non-trivial synchrony structure between neurons (Câteau et al 2008), and that dendritic delays play an important role (Senn et al 2002;Lubenov and Siapas 2008). The present framework can be adapted to incorporate these aspects.…”
Section: Discussionmentioning
confidence: 98%
“…This has only begun to be addressed for STDP as well as for synaptic plasticity in general (Karbowski and Ermentrout 2002;Masuda and Kori 2007), mainly using numerical simulation (Song and Abbott 2001;Morrison et al 2007). A particular effort was made to understand how STDP can modify synchrony properties in neuronal networks (Senn et al 2002;Câteau et al 2008;Lubenov and Siapas 2008). In recent articles (Burkitt et al 2007;Gilson et al 2009c), we have developed a theoretical framework to model the weight dynamics in a network with any arbitrary architecture and carried out the analysis for the case of a recurrently connected network with no external inputs, both for full and partial connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports claim the relevance of acausal spike pairs in the presence of synaptic delay [10,28]. This and other factors, such as different time scales of LTP and LTD [27], may let bidirectional synapses survive as observed in in vitro experiments [29].…”
Section: Discussionmentioning
confidence: 99%
“…The study of the neuronal dynamics induced by STDP in recurrent architectures is therefore a crucial step in order to gain insight into learning in the brain. However, the study of STDP in such recurrent networks has only begun to be addressed, mainly using numerical simulation (Song and Abbott 2001;Senn et al 2002;Wenisch et al 2005;Morrison et al 2007;Lubenov and Siapas 2008;Câteau et al 2008;Kang et al 2008). There exists only a few theoretical results for recurrent architectures (Karbowski and Ermentrout 2002;Masuda and Kori 2007) due to mathematical difficulties in evaluating the effect of feedback synaptic loops.…”
Section: Introductionmentioning
confidence: 99%